Antibiotic prescribing trends in the emergency department for veterans with spinal cord injury and disorder 2002–2007. (September 2013) - Evans, Charlesnika T.; Rogers, Thea J.; Chin, Amy; Johnson, Stuart; Smith, Bridget; Weaver, Frances M.; Burns, Stephen P.
Abstract : Objective: Clinical guidelines exist to promote antibiotic stewardship, particularly in ambulatory care settings such as the emergency department (ED). However, there is limited evidence on prescribing practice for persons with spinal cord injury and disorder (SCI/D). The goal of this study was to assess trends in antibiotic prescribing in the ED setting for persons with SCI/D. Design: A retrospective dynamic cohort study design. Setting: ED visits that did not result in same day hospitalization over 6 years (fiscal year (FY) 2002-FY2007) in Department of Veterans Affairs (VA) facilities Participants: Veterans with SCI/D. Outcome measures: VA clinical and administrative databases were used to identify the cohort and to obtain demographics, diagnoses, and medications. The rate of antibiotic prescribing for ED visits was defined as the number of antibiotics/total ED visits. Results: Veterans with SCI/D had 21 934 ED visits and 5887 antibiotics prescribed over the study period (rate of 268.4 prescriptions/1000 visits). The antibiotic prescribing rate increased from 238.8/1000 visits in FY2002 to 310.8/1000 visits in FY2007 ( P < 0.0001). This increase in the rate of prescribing was seen across all patient demographics and factors assessed. Conclusion: Although clinical guidelines for judicious use of antibiotics in persons with SCI/D have been disseminated to providers, antibiotic prescribing in an ED setting is high and continuing to rise in this population.